Formulasi Dan Evaluasi Sediaan Gummy Candies Mengandung Infusa Daun Jambu Biji (Psidium guajava L.) Dengan Variasi Konsentrasi Sukrosa - Christiningtyas Eryani, Mikhania; Judy Handojo, Kukuh; Safitri, Manzil; Husni, Patihul (JURNAL FARMASI GALENIKA, 2024)
Guava leaves (Psidium guajava L.) are a traditional medicine used to treat diarrhea. The subtance contained in guava leaves that can have antidhiarrheal properties is tannin. Gummy candies are sweet product made from the main gel- forming ingredients such as gelatin, carrageenan, jelly, as well as sweetening ingredients such as sucrose, lactose, glukose, and others. This research aims to formulate and evaluate guava leave infused gummy candies with varying sucrose concentrations of 15 (F1)%, 20% (F2), and 25% (F3). Test data for the organoleptic physical properties of F1, F2, and F3 are chewy texture, weak melon aroma, green color, and sweet taste. In the weight uniformity test there was no difference between F1, F2, and F3. The average pH test results where F1 is 5.81, F2 is 6.16 and, F3 is 6.63. Testing the water content of gummy candies resulted in average of F1 is 12.4%, F2 is 27.5, and F3 is 43,29%. The conclusion is variation concentration of sucrose affect pH and water content but its not affect organoleptic and weight uniformity of gummy candies.